How do radiation oncology health professionals inform breast cancer patients about the medical and technical aspects of their treatment? - Halkett, Georgia; Short, M.; Kristjanson, Linda (Elsevier, 2009)
Background and Purpose: Radiation therapy patients need information to make treatment decisions, understand treatment and manage side effects. The purpose of this study was to: (1) Identify information about radiation therapy routinely provided to breast cancer patients; (2) Determine which health professionals provide information; (3) Examine whether information is routinely provided at the same time points and (4) Determine whether health professionals and patients place similar importance on specific information.Materials and Methods: Health professionals in radiation therapy departments in Australia and New Zealand completed self-administered questionnaires. Results were analysed and compared to patient responses from a previous study. Results: Forty-one of 52 departments participated in this survey. Information provision was inconsistent between departments in terms of how and when information was given. Although the types of information provided to patients appeared to align with patients' needs, health professionals and patients placed different levels of importance on specific information. Conclusions: A wide range of information is provided to patients. However, the priority given to different information needs and the focus of information provision may not be optimal from the perspectives of patients. Further research needs to be conducted to determine patients information needs and develop specific information resources tailored to meet these needs.